Sustainability Assessment of Marine Economy in China: Spatial Distributions of Marine Environmental Governance Entities in Shanghai - Yang, Debin; Geng, Hong; Fu, Yan-Kai; Zhu, Ting (Frontiers in Environmental Science, 2022)
The amount of investment in marine environmental governance (MEG) is growing fast in China, which brought the prosperity of environmental treatment entities (e.g., water treatment enterprises and port pollution control institutions). Based on spatial big data, this paper adopted kernel density method, standard deviational ellipse, and nearest neighbor index to explore the spatial distribution pattern of MEG entities in Shanghai from 2005 to 2021. Several conclusions emerged from this study: (1) From 2005 to 2021, the new MEG entities in Shanghai have increased by more than 10 times; (2) The analysis showed that the nearest neighbor index of Shanghai’s MEG entities was larger than 0.2, with Z values all being lower than −30, indicating that the spatial agglomeration characteristics in Shanghai was significant at an alpha level of 1%. (3) Chongming District, Pudong New District, Fengxian District, and Minhang District were the core agglomeration areas. (4) The standard deviational ellipse analysis suggested that the distribution of Shanghai MEG entities from 2005 to 2021 showed an obvious pattern of spreading from the center to both the north and south. This results in an industrial belt along the Huangpu River. This paper argues that the spatial distribution of MEG entities in Shanghai confirms the central place theory, which highlights the network characteristics that combine centrality with spreading to the surrounding areas.